2022
DOI: 10.3390/ani12111448
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Survey Study on the Use of Locoregional Anaesthesia in Non-Conventional Species: Current Practice and Potential Future Developments

Abstract: The objectives of this study were to investigate the current attitudes of veterinarians towards the use of locoregional anaesthesia in non-conventional animal species and to identify areas for future useful research on this topic. A questionnaire was circulated online. A total of 417 veterinarians, including American and European specialists/specialists-in-training in both zoological medicine and anaesthesia/analgesia (ACZM/ECZM and ACVAA/ECVAA), participated in the study. Fifty-nine percent of respondents per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…In less common species literature is scarce and we do not take full advantage of the regional anaesthesia technique already described in dogs. Even so, an observational survey study involving a significant portion of respondents (over one-third) revealed that many use adapted regional anaesthesia techniques for pain management in birds [4]. However, what limits the use of these techniques in these species are the lack of published data on the local anaesthetic drugs and regional anaesthetic techniques and limited knowledge of anatomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In less common species literature is scarce and we do not take full advantage of the regional anaesthesia technique already described in dogs. Even so, an observational survey study involving a significant portion of respondents (over one-third) revealed that many use adapted regional anaesthesia techniques for pain management in birds [4]. However, what limits the use of these techniques in these species are the lack of published data on the local anaesthetic drugs and regional anaesthetic techniques and limited knowledge of anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Pain management in avian surgery is a rapidly evolving field, mirroring advancements made in mammalian regional analgesia techniques. Ultrasound and nerve stimulatorguided techniques have been previously described for application in both domestic [1,2] and wild avian populations [3,4]. Notably, extensive research conducted in canines has provided a valuable foundation for adapting nerve identification and blockade techniques for use in avian species.…”
Section: Introductionmentioning
confidence: 99%